Elemental Profiling of Soil Adhered to Footwear Using ICP-MS for Forensic Applications - นวมสุคนธ์ พรทิพย์; ชูสกุลเกรียง ศิริรัตน์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
Soil is an important type of trace evidence in forensic science because its geochemical composition reflects specific locations and can help link individuals to crime scenes. This study examined the elemental composition of soil adhered to footwear and evaluated the potential of Inductively Coupled Plasma Mass Spectrometry (ICP-MS) for soil discrimination. Five soil types-lateritic, sandy, saline, muddy, and loamy soils were collected from Samut Songkhram Province. A controlled walking simulation was performed on a 1 × 1 m area, and soil attached to shoe soles was collected for analysis. Twenty-seven elements were determined after microwave-assisted digestion. Data were analyzed using descriptive statistics, one-way analysis of variance (ANOVA) at a significance level of 0.05, and principal component analysis (PCA). The results showed significant differences in some elements among soil types (p < 0.05). PCA also clearly separated the sample groups, with samples from the same soil type clustering in similar directions along the principal component axes. These findings indicate that soil recovered from footwear retains source-specific elemental characteristics and can be used for forensic soil comparison.